A Quarter-Century of Normalization and Social Role Valorization Evolution and Impact - Flynn, Robert J. (University of Ottawa Press / Les Presses de l'Université d'Ottawa, 1999)
During the late 1960s, Normalization and Social Role Valorization (SRV) enabled the widespread emergence of community residential options and then provided the philosophical climate within which educational integration, supported employment, and community participation were able to take firm root. This book is unique in tracing the evolution and impact of Normalization and SRV over the last quarter-century, with many of the chapter authors personally involved in a still-evolving international movement.